The first Polish total laryngectomies - Kierzek, Andrzej; Paprocka-Borowicz, Małgorzata; Pozowski, Andrzej; Kuciel-Lewandowska, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2013)
The total removal of the larynx (total laryngectomy), performed in 1872 by the well-known Viennese surgeon Christian A. Theodor Billroth (1829–1894), was an epoch-making event in the history of surgery and laryngology. This paper presents the first surgeons who performed this operation. The first Pole who performed a total laryngectomy (1877) was Julian Kosiński (1833–1914), head of the Surgical Clinic of Imperial University Warsaw. It was the 14th operation of this kind in the world. Several laryngectomies were carried out by Franciszek Ksawery Jawdyński (1851–1896), called the father of Polish head and neck surgery, who was the first Pole to excise a malignant neck cancer together with the lymph nodes. The next total laryngectomies were performed by the following Polish surgeons: Jan Mikulicz-Radecki (1850–1905), Władysław H.S. Krajewski (1855–1907), Alfred Obaliński (1843–1898). According to Jan Sędziak, by 1897 Poland with 16 laryngectomies (per 188 carried out) had occupied the fourth position in the world. The failures of the first laryngectomies were due to such factors as the ignorance of shock pathophysiology, the inability to ensure the patency of the airways during and after the operation, which would result in lung and mediastinum infections, massive haemorrhages and so on. But the primary cause was the lack of constructive collaboration between the laryngologists and the surgeons.